The use of handheld mobile devices : an exploratory study of English Language student educators - Lediga, Mamaroba Sylvia (My University, 2018)
This study explores the use of handheld mobile devices in the learning and teaching of English language. The problem is that students have to stand in long queues at computer laboratories because the space is limited and they have to take turns in using the computers. Second level English student educators participated in the study; they responded to a questionnaire and sat for test on the use of mobile handheld devices. The study is underpinned by the integration of the Activity Theory and Social Constructivism. The solution is that mobile handheld devices can be used to provide access to learning material and just-in-time information outside and inside the formal class time and space because findings of the study show that almost all second level student educators at the University of Limpopo possess and use handheld mobile devices.
Thesis ((M. A. (English Studies)) -- University of Limpopo, 2018
Keywords: Handheld mobile devices; English language; Computers; Internet; Educational technology; Computer-assisted instruction; Internet in higher education; Electronic book readers; Engilsh language -- Study and teaching; Teaching -- Aids and devises